Dispensasi Pernikahan Dini Pasca Revisi Undang-Undang Perkawinan di Indonesia - Fitriyani; Abd. Basir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
This study aims to determine the form of marriage dispensation after the revision of the marriage law by examining the factors that cause marriage dispensations and the implications of marriage dispensations on family life. The method used in this paper is based on a literature review and analyzed descriptively and qualitatively. The results show that the cause of early age marriage comes from the individual factors of the child himself and the factors of his parents. The existence of early marriage has psychological and social implications for children, parents, and the surrounding environment. Therefore, to reduce the prevalence of early marriage, strategic steps are taken jointly by the family, the Office of Religious Affairs, the government, religious leaders, and other community leaders.